(untitled) (Fisioterapia e Pesquisa, 2022)
Standing posture during work has been associated with musculoskeletal symptoms. However, few studies assess standing time using objective measures. Thus, the aim of this study was to verify whether standing time at work is associated with low back and lower limbs pain in the last seven days and 12 months in elderly caregivers and cleaners. This is a cross-sectional study. Standing time at work was quantified using inclinometers attached to the workers’ thigh and spine. Musculoskeletal symptoms were assessed using the Nordic Musculoskeletal Questionnaire. Data were analyzed using the point biserial correlation (rpb) between standing time at work and the presence of musculoskeletal symptoms. The analyzes were performed using the SPSS software and the level of significance adopted was 5%. Workers spend most of their time standing still (41.3%) or walking (39.3%). There was a positive correlation between the presence of symptoms in the lower back and standing time (rpb=0.52; p<0.05). There was a negative correlation between walking time and symptoms at the hip (12 months) (rpb=-0.53; p<0.05) and running time and symptoms at the hip (seven days) (rpb=-0.43; p<0.05) and lower back (rpb=-0.43; p<0.05). Longer standing time was correlated with the presence of symptoms in the lower back. Meanwhile, less time walking and running correlated with the presence of musculoskeletal symptoms in the hips and lower back